The efficacy of prophylactic clip closure of mucosal defects after colorectal endoscopic submucosal dissection on delayed bleeding. (3rd October 2021) - Miyakawa, Akihiro; Kuwai, Toshio; Sakuma, Yukie; Kubota, Manabu; Nakamura, Akira; Itobayashi, Ei; Shimura, Haruhisa; Suzuki, Yoshio; Shimura, Kenji
Abstract: Objective: Although prophylactic clip closure after endoscopic mucosal resection may prevent delayed bleeding, information regarding colorectal endoscopic submucosal dissection (CR-ESD) is lacking. Therefore, this study evaluated the effect of prophylactic clip closure on delayed bleeding rate after CR-ESD. Materials and methods: A total of 614 CR-ESD procedures performed in 561 patients were retrospectively reviewed. The primary outcome, which was delayed bleeding rate, was analyzed between the prophylactic clip closure and non-closure groups. Furthermore, the predictors of delayed bleeding were also evaluated. Results: The patients were divided into the clip closure group ( n  = 275) and non-closure group ( n  = 339). Delayed bleeding rate was significantly lower in the closure group than in non-closure group (6 cases [2.2%] vs. 20 cases [5.9%], p  = .026). The univariate logistic regression analyses revealed that delayed bleeding was significantly associated with laterally spreading tumor-granular-nodular mixed type (LST-G-Mix; odds ratio [OR], 3.77; 95% confidence interval [CI], 1.70–8.34; p  = .001). By contrast, prophylactic clip closure was significantly associated with low delayed bleeding rate (OR, 0.36; 95%CI, 0.14–0.90; p  = .029). The multivariate logistic regression analyses revealed LST-G-Mix as a significant independent delayed bleeding predictor (OR, 3.25; 95%CI, 1.45–7.32; p  = .004), whereas, prophylactic clip closure was identified as a significant independent preventive factor of delayed bleeding (OR, 0.39; 95%CI, 0.15–1.00; p  = .049). Conclusions: Prophylactic clip closure after CR-ESD is associated with low delayed bleeding rate. LST-G-Mix promotes delayed bleeding, and performing prophylactic clip closure may be advisable.